Leadership In Surgical Science: Literature Review - Sukasah, Chaula Luthfia; Aulia, Indri; Sani, T. Fadli Nazwan (Lingkar Studi Bedah Plastik Foundation, 2019)
Background : A Surgeon should have good leadership. Leadership plays an important role in improving health services. Leadership can shape a better future. Method : A literature search was conducted in November 2019. Related keywords were applied to Pubmed, Medline, and SCOPUS for studies published in the last five years. Relevant research is taken to be used as the discussion material. Result : The key to surgical leadership is collaboration and cooperation, humanism and mentorship, and operational efficiency. Conclusion: Effective leadership in a surgical team has the following characteristics: (1) Defines the role of a leader clearly, especially in critical situations; (2) Leadership style that suits the clinical situation; (3) Clear directions to team members; (4) Consistently seeking input from team members; (5) Involving members in decision making.